Juvenile xanthogranuloma associated with osteogenesis imperfecta type 1B. - Mishra, S.N.; Nayak, C.S.; Deshpande, D.J.; Dhurat, R.S.; Topal, A.A. (European Journal of Pediatric Dermatology, 2010)
A 5 months old baby girl presented with one month history of multiple skin colored asymptomatic raised lesions over face, scalp, back and abdomen, and multiple fractures involving long bones without significant preceding trauma. On clinical examination she had blue sclerae and low hair line. The skin lesions healed spontaneously in the following 2 to 3 months. She later showed signs of dentinogenesis imperfecta, hyperextensible wrists, umbilical hernia and hearing loss. Histopathology of a skin lesion showed a dense, non encapsulated, well demarcated foamy histiocytic infiltrate with eosinophils, lymphocytes and dermal fibrosis. Her radiological examination revealed diffuse osteopenia, bowed and fractured femur bone and hepatosplenomegaly. To the best of our knowledge, this is the first case of juvenile xanthogranuloma with osteogenesis imperfecta type 1B reported in literature.